Resolving P.W. Botha’s 1985 Rubicon riddle (Historia, 2021)
President P.W. Botha's notorious "Rubicon" speech on 15 August 1985 at the National Party Congress in Durban was probably one of the most significant speeches in the history of South Africa. It was supposed to break the political and military deadlock between the apartheid government and the banned liberation movements, notably the ANC. Botha was widely expected to announce new policies that could possibly have ended the political conflict in the country. However, that did not happen. Instead the speech was a total fiasco. Until now, one could only speculate why this was so. Original correspondence between P.W. Botha and ministers Pik Botha and Chris Heunis and a secret, verbatim transcript of the notorious preparatory 'Sterrewag' (Pretoria Astronomical Observatory) meeting of 2 August 1985, now confirm that the South African government and P.W. Botha were not ready for such policy breakthrough announcements and had never planned to make them.
Keywords: Rubicon speech; Sterrewag; black political reform; power sharing; onstitutional development